Transforming Experiential Learning in the Honors Interpersonal Communication Course: Interpersonal Enrichment Journeys During the COVID-19 Pandemic and Beyond - Jennifer A. H. Becker (Central States Communication Association, 2023)
Drawing upon my own experience as an educator, I describe and reflect upon my experiential learning-pedagogical process of transforming my fall 2020 Zoom-based honors interpersonal communication course in which my students traversed through a series of experiential learning activities called Interpersonal Enrichment Journeys. Quantitative and written data revealed that students achieved desired learning outcomes and strengthened much-needed interpersonal connections despite the circumstances and stressors induced by the pandemic. Interpersonal Enrichment Journeys can be replicated to maximize the features of quality online courses identified by Kaufman and Vallade (2022), such as helping students develop personal connections in a positive learning climate and ensuring that "students are getting the information and interaction they need to be successful" (p. 153).